2006
DOI: 10.3928/1081-597x-20061102-03
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront Analysis in Asian-Brazilians

Abstract: PURPOSE: To compare the distribution of ocular higher order wavefront aberrations (third to sixth order) in the Brazilian population of Asian and non-Asian refractive surgery patients. METHODS: Preoperative refractive and wavefront data were reviewed for 648 eyes in 324 patients who underwent custom ablation at the Excimer Laser Santa Cruz refractive surgery center in São Paulo, Brazil, from March 2002 to July 2005. Patients were divided into two groups: Asian patients and non-Asian patients, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
1
10
0
1
Order By: Relevance
“…The magnitude of corneal spherical aberration found in this study was similar to that previously reported in a group of senile cataract patients 13 . It is reported that spherical aberration is not associated with high degrees of myopia, 14 and no difference in spherical aberration is noted between Asian and non‐Asian patients 15 . Before surgery, the mean corneal spherical aberrations in aspheric and spherical groups were 0.30 ± 0.11 and 0.29 ± 0.13 µm, respectively, for 6‐mm pupil diameter.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The magnitude of corneal spherical aberration found in this study was similar to that previously reported in a group of senile cataract patients 13 . It is reported that spherical aberration is not associated with high degrees of myopia, 14 and no difference in spherical aberration is noted between Asian and non‐Asian patients 15 . Before surgery, the mean corneal spherical aberrations in aspheric and spherical groups were 0.30 ± 0.11 and 0.29 ± 0.13 µm, respectively, for 6‐mm pupil diameter.…”
Section: Discussionsupporting
confidence: 90%
“…13 It is reported that spherical aberration is not associated with high degrees of myopia, 14 and no difference in spherical aberration is noted between Asian and non-Asian patients. 15 Before surgery, the mean corneal spherical aberrations in aspheric and spherical groups were 0.30 Ϯ 0.11 and 0.29 Ϯ 0.13 mm, respectively, for 6-mm pupil diameter. This is similar to the investigation that the mean corneal spherical aberration was 0.32 Ϯ 0.12 mm at a 6-mm pupil size in 70 eyes of 70 cataract patients aged from 32 to 89 years.…”
Section: Discussionmentioning
confidence: 93%
“…Measurement of the HOA profile can be affected by multiple factors including pupil size, cycloplegia, age, ethnicity, ocular surface status, and the device used. 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 …”
Section: Introductionmentioning
confidence: 99%
“…The HOA profiles of Caucasian, Asian Chinese, Asian Indian, and Brazilian eyes have been documented in the literature. 22 23 24 25 26 27 28 However, other than a study measuring corneal spherical aberration, there are no studies in the literature to evaluate the total ocular wavefront profile in Arab eyes. 29 In this study, we evaluate the ocular (whole eye) wavefront profile of refractive surgery candidates of Arab origin and compare it to candidates of South Asian (Indian sub-continent) origin.…”
Section: Introductionmentioning
confidence: 99%
“…(7,8) As complicações do LASIK se concentram na confecção da lamela, o que não ocorre com a PRK, e no risco de enfraquecimento biomecânico da córnea resultando em uma possível indução de ectasia corneana iatrogênica. (9,10) A técnica PRK também não é isenta de complicações, a exemplo da formação de opacidade corneana no pós-operatório, geralmente secundária a correção de altos graus de miopia. (11,12) A imposição de limites na profundidade de fotoablação dos olhos submetidos a PRK e as modernas plataformas de excimer laser contribuíram para uma sensível diminuição da incidência de opacidades corneanas.…”
Section: Introductionunclassified